PROPHYLAXIS OF TEETH AND ORAL CAVITY DISEASES - Marjona MARDONOVA (Scholar Express Journal, 2023)
This article provides a general understanding of oral hygiene and general rules for oral hygiene. A number of recommendations for proper dental care and disease prevention are also given
Keywords: stomatology; pathogen; tissue disease; irrigator